Proposals for the classification of chronic (mature) B and T lymphoid leukaemias. French-American-British (FAB) Cooperative Group. Issue 6 (June 1989) - Bennett, J M; Catovsky, D; Daniel, M T; Flandrin, G; Galton, D A; Gralnick, H R; Sultan, C
Abstract : Peripheral blood, bone marrow films, and bone marrow biopsy specimens from 110 patients, well characterised by clinical and laboratory studies, including electron microscopy, were reviewed, to determine proposals for the classification of chronic (mature) B and T cell leukaemias. On the basis of cytology and membrane phenotype the following disorders were defined: (i) B cell type: chronic lymphocytic leukaemia (CLL); CLL of mixed cell type, which includes cases with more than 10% and less than 55% prolymphocytes (CLL/PL), and a less well defined form with pleomorphic lymphocytes but less than 10% prolymphocytes; prolymphocytic leukaemia (PLL); hairy cell leukaemia (HCL); HCL variant; splenic lymphoma with circulating villous lymphocytes; leukaemic phase of non-Hodgkin's lymphoma (follicular lymphoma, intermediate, or mantle zone lymphoma and others); lymphoplasmacytic lymphoma with peripheral blood disease (mostly Waldenström's macroglobulinaemia); and plasma cell leukaemia. (ii) T cell type: T/CLL, which was differentiated from reactive T/lymphocytosis; T/PLL; adult T cell leukaemia/lymphoma; and Sézary's syndrome. The recognition of distinct entities within the B and T cell leukaemias seems to have clinical and epidemiological connotations. It is hoped that these proposals may serve as the basis for further work, discussion, and improved management of patients.